PENGARUH KEMAMPUAN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN DI PERUSAHAAN DAERAH AIR MINUM KABUPATEN JENEPONTO - Andi Pattarani (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to 1) find out the description of the ability of human resources in the Regional Water Company of Kab. Jeneponto, 2) to know the description of the performance of employees in the Regional Water Company of Kab. Jeneponto and 3) determine the effect of human resource capabilities on improving employee performance at the Regional Water Company of Kab. Jeneponto. This research is a survey research with a total population of 67 employees in the Regional Water Company of Jeneponot Regency. Sampling in this study used a stratified proportional random sampling technique, by taking 40% of the total population so that the number of samples was 26. The results of the study show that 1) The description of the ability of human resources in the Regional Water Company of Jeneponto Regency is in the medium category, 2) the description of the performance of the employees in the Regional Water Company of the Jeneponto Regency is in the medium category and 3) The influence of the ability of human resources on the performance of the employees in the Regional Water Company. Drinking Jeneponto Regency shows a significant correlation.